Pyura (Tunicata: Ascidiacea: Pyuridae) on the coasts of Panama - Rocha, Rosana M.; Counts, Bailey Keegan (Zootaxa, 2019)
Recent efforts have been taken to survey and describe the ascidian fauna of the Pacific and Atlantic coasts of Panama; however, the genus Pyura still remains poorly known. Sampling events have been occurring since 2003. In this research, we describe two new species from the Atlantic coast of Panama: P. longispina sp. nov., P. lopezlegentilae sp. nov., and two new species from the Pacific Coast of Panama: P. carmanae sp. nov. and P. imesa sp. nov. We also supply a tabular key for all the Pyura species found in Panama.